Perancangan Sistem Informasi Persediaan Metode First In First Out Berbasis Web - Nur Inayah; Sri Wahyuning; Jarot Dian Susatyono (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2024)
An accounting system that includes the organization of forms, records and reports that are focused in such a way as to provide information related to finance that is really needed by management to make it easier for company managers. A well-structured accounting system will also provide good meaning for management in managing its business. Every company has several accounting systems that are interrelated and work together to achieve certain goals. Inventory is arranged in staggered form (list/table), while the balance sheet is presented using accounts. Inventory is the basis for compiling balance sheets and annual financial reports. Aruna Cosmetics is engaged in trading various kinds of cosmetics, carrying out simple inventory records using a calculator and transferring them into books, which results in inefficient performance. When prices rise, the FIFO method causes too little effort and tends to overvalue inventory assets compared to direct individual valuation. However, if the actual movement of capital occurs on the basis of the FIFO principle, then the assessment of this method corresponds to a direct individual assessment. The formation of hidden reserves when prices rise is not possible with the FIFO method. An increase in profits due to an increase in the price of inventory is called inventory profit or illusory profit.